9(x-2)+8=4x+5(-2+x)

Simple and best practice solution for 9(x-2)+8=4x+5(-2+x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9(x-2)+8=4x+5(-2+x) equation:


Simplifying
9(x + -2) + 8 = 4x + 5(-2 + x)

Reorder the terms:
9(-2 + x) + 8 = 4x + 5(-2 + x)
(-2 * 9 + x * 9) + 8 = 4x + 5(-2 + x)
(-18 + 9x) + 8 = 4x + 5(-2 + x)

Reorder the terms:
-18 + 8 + 9x = 4x + 5(-2 + x)

Combine like terms: -18 + 8 = -10
-10 + 9x = 4x + 5(-2 + x)
-10 + 9x = 4x + (-2 * 5 + x * 5)
-10 + 9x = 4x + (-10 + 5x)

Reorder the terms:
-10 + 9x = -10 + 4x + 5x

Combine like terms: 4x + 5x = 9x
-10 + 9x = -10 + 9x

Add '10' to each side of the equation.
-10 + 10 + 9x = -10 + 10 + 9x

Combine like terms: -10 + 10 = 0
0 + 9x = -10 + 10 + 9x
9x = -10 + 10 + 9x

Combine like terms: -10 + 10 = 0
9x = 0 + 9x
9x = 9x

Add '-9x' to each side of the equation.
9x + -9x = 9x + -9x

Combine like terms: 9x + -9x = 0
0 = 9x + -9x

Combine like terms: 9x + -9x = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| 6[3-(-8x-2)]=240x+78 | | 3(x-2)=5(x-3)+2 | | A+(-35)=75 | | 6(3n-1)+9=3(6n+3) | | 2x+4-7(x+1)=3x+4 | | 4y^2+x=0 | | -23/24=11/12+5x/6 | | 2.5x-8.8=-14.8+1.5x | | 5+35x=15x+53 | | 4b=30 | | -2y-17-22=2y+3y(y-6) | | 12+3x/5=39 | | 17000=-0.75x^2+255x-1000 | | x^2-8=4x+4 | | 3a^2-13a=10 | | 72.00+x=79.84 | | 3x^2=14-19x | | 1.6x=24 | | 16z^4+64p^4+24z^3-55zp^2-48zp^3= | | k*3=6 | | 2x+6=-30-4x | | -3x/10=-4/5 | | 10t-19=6t-11 | | 4z+3z=6z+8 | | x-433.42=53.52 | | 3+(4+5)=(3+4)+m | | -5(n+3)-(3+3n)=-9n | | 5-(3y-7)= | | 5x+36=20 | | 0=2+1.5x | | 12n+11=0 | | x-(90+0.3x)=0.2x |

Equations solver categories